2017
DOI: 10.3892/mmr.2017.7633
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin potentiates TRAIL-induced apoptosis through p38 MAPK activation and intracellular reactive oxygen species production

Abstract: The combination of tumor necrosis factor‑related apoptosis‑inducing ligand (TRAIL) with other agents has been recognized as a promising strategy to overcome TRAIL resistance in cancer cells. Baicalin (5, 6‑dihydroxy‑7‑o‑glucuronide flavone) is a flavonoid from the root of the medicinal herb Scutellaria baicalensis Georgi, which has been reported to exert antioxidant, anti‑inflammatory, antiviral and anticancer activities in vitro. However, the effect of baicalin on TRAIL‑induced cytotoxicity has not been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Phosphorylation of p38 is a signaling mechanism where most of the flavonoids exert their effect. 43,44 In the current study, we also found that FGL could induce phosphorylation of p38. RELA is a transcription factor.…”
Section: Discussionsupporting
confidence: 76%
“…Phosphorylation of p38 is a signaling mechanism where most of the flavonoids exert their effect. 43,44 In the current study, we also found that FGL could induce phosphorylation of p38. RELA is a transcription factor.…”
Section: Discussionsupporting
confidence: 76%
“…9, 10) indicated involvements of MAPK, SYK, and PI3K as targets of baicalin. This result is in accordance with previously reported studies that baicalin inhibits p38 MAPK, and this mechanism may be responsible for its anti-inflammation effect [23,25,43,44]. MAPK is activated under the stress of cytokine; therefore, inhibiting MAPK is a promising approach for hyper-inflammatory disease, such as COVID-19 [45].…”
Section: Discussionsupporting
confidence: 92%
“…However, in mammalian cells (e.g., CHO cell), baicalin could reduce ROS production [ 69 ]. There are also reports showing that baicalin induces apoptosis in human non-small lung cancer cells and osteosarcoma cells through ROS production [ 70 , 71 ]. Baicalin could protect mitochondria from damage caused by streptozotocin and hepatic ischemia/reperfusion and increase the activity of citrate synthase in rats [ 72 , 73 ].…”
Section: Compounds Targeting Mitochondriamentioning
confidence: 99%